PENERAPAN METODE DISKUSI KELOMPOK PADA MATA PELAJARAN MATEMATIKA KELAS 4 SDN GADANG 3 KOTA MALANG - Salsabilah, Ana Nur; Suwandayani, Beti Istanti; Mar'atin Nuro, Falistya Roisatul; Ulum, Bahrul (Universitas Negeri Medan, 2023)
The purpose of this study was to find out how the learning strategies and media were used to teach grade 4 mathematics at Gadang 3 Elementary School, Malang City. This research uses a descriptive qualitative research type. Data collection techniques in this study were by means of interviews, observation, and documentation. The subjects of this study were grade 4 teachers. The data analysis techniques used were data collection, data reduction, data display, and veryfying. The results of this study indicate that the existence of learning strategies in the form of study groups and joint discussions can improve student learning outcomes due to the heterogeneity of each group which encourages participants to learn competitively but still fun. Students are asked to help each other between friends so that other students do not feel left behind by the others. In addition to learning strategies, the learning media used are also the result of student designs, this makes students able to easily use these learning media. Learning media is also made of materials that are easily found around. Prior to implementing the study group strategy, grade 4 teachers had implemented several strategies. However, the class teacher considers this strategy to be the most effective in learning, especially in mathematics.